2016
DOI: 10.1007/s12154-016-0162-8
|View full text |Cite
|
Sign up to set email alerts
|

2-(chromon-3-yl)imidazole derivatives as potential antimicrobial agents: synthesis, biological evaluation and molecular docking studies

Abstract: A series of novel 2-(chromon-3-yl)-4,5-diphenyl-1H-imidazoles (4a-h) were synthesized by one pot condensation of substituted 3-formylchromones (1a-h), benzil (2) and ammonium acetate (3) in refluxing acetic acid at 110°C under N2 atmosphere. Allylation of compounds 4a-h with allyl bromide in the presence of fused K 2 CO 3 furnishedThe synthesized compounds were characterized spectroscopically and evaluated for in vitro antimicrobial activity against various pathogenic bacterial and fungal strains by disc diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It was thus found that compound 431a (R 1 = R 2 = R 3 = H) and compound 428c (R 1 = R 2 = H, R 3 = Cl) exhibited excellent inhibitory activity against B. subtilis with MIC values of 2.4 and 3.2 µM, respectively. Compound 431a also displayed significant inhibitory activity against E. coli with an MIC value of 2.8 µM [249].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was thus found that compound 431a (R 1 = R 2 = R 3 = H) and compound 428c (R 1 = R 2 = H, R 3 = Cl) exhibited excellent inhibitory activity against B. subtilis with MIC values of 2.4 and 3.2 µM, respectively. Compound 431a also displayed significant inhibitory activity against E. coli with an MIC value of 2.8 µM [249].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Ishar and coworkers synthesised and characterised novel 3-(4,5-diphenyl-1H-imidazol-2-yl)-4H-chromen-4-ones 428 by one pot condensation of substituted 4-oxo-4H-chromene-3-carbaldehydes 429, benzil (161), and AcONH 4 in refluxing AcOH under N 2 atmosphere (Scheme 89) [249]. The subsequent reaction of compounds 428, which were obtained in yields ranging from 78 to 84%, with allyl bromide (430) in DMF at room temperature for 24 h in the presence of fused K 2 CO 3 furnished 3-(1-allyl-4,5-diphenyl-1H-imidazol-2-yl)-4H-chromen-4-ones 431 in yields ranging from 50 to 62%.…”
Section: Addendummentioning
confidence: 99%
“…Because the heterocyclic ring includes the core of the active moiety or pharmacophores, we have been interested in working on structural modification of imidazole and benzimidazole. Besides this, these two heterocyclics containing nitrogens can be substituted in different positions to give several compounds with antibacterial activity [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…Imidazole is a versatile heterocyclic compound with high therapeutic properties and a broadened scope that encouraged Medicinal Chemists to synthesise numerous novel chemotherapeutic agents as anti-cancer [20][21], anti-oxidant [22][23], anti-inflammatory [24][25], anti-microbial [26][27], anti-tubercular [28], anti-diabetic [29][30], antimalarial [31], HMG-CoA reductase inhibitory activity [32], anti-protozoa [33], anti-HIV [34], anticonvulsant [35][36]. It is a ubiquitous moiety in agricultural, medicinal, and industrial chemistry.…”
Section: Introductionmentioning
confidence: 99%